Examining metrics and methods for determining critical facility system effectiveness. (2nd June 2010) - Hester, Patrick T.; Adams, Kevin MacG.; Mahadevan, Sankaran
Approaches for quantifying security system performance vary for different critical facilities, ranging from in-depth quantitative analyses to heuristics-based rules of thumb. Since there is no single accepted definition for what constitutes an effective security system for a critical facility and how best to design and analyse these systems, this technical note is a survey of potential metrics and methods for critical facility system effectiveness. Recommendations are made for which metric is best suited for critical facility system effectiveness and a new method is recommended for evaluating system effectiveness.